PENGARUH PELATIHAN ETIKA PROFESI TERHADAP KESADARAN DAN KEPATUHAN AKUNTAN PUBLIK DALAM MENJALANKAN TUGAS - Yunus Tulak Tandirerung (Bajang Institute, 2025)
This study examines the effects of professional ethics training, the effectiveness of instruction, the expansion of educational programs, and the understanding of ethical standards in relation to public ethics and ethics education. Utilizing the Partial Least Squares (PLS) method with 575 respondents, analysis was conducted to assess the correlation between the variables. The research results indicate that effective ethics education and comprehensive educational programs significantly increase public awareness of professional ethics. In addition to this, education about ethical standards has a positive impact on increasing accountancy through increased deduction. All of this suggests that high-quality education is crucial to developing public awareness and trust in the profession of akuntansi by preparing public servants in accordance with professional standards